Optimizing MSME Marketing through Social Media: A Maqashid asy-Sharia Perspective - Mad Heri; Mardhiyah Hayati; Is Susanto (Pascasarjana IAIN Metro, 2025)
This study aims to analyze the optimization of marketing strategies through social media for the development of Micro, Small, and Medium Enterprises (MSMEs) in Lampung Province from the perspective of Maqashid asy-sharia. Employing a qualitative descriptive method, data collection was conducted through interviews and observations with MSME owners and relevant stakeholders. The results of this study indicate that: (1) the utilization of social media as a marketing tool has proven to be highly effective in expanding the reach of MSMEs, enhancing brand awareness, and increasing consumer engagement; (2) marketing through social media aligns with the principles of Maqashid asy-sharia, particularly in preserving wealth (hifdz al-mal) and ensuring ethical business practices. Furthermore, this study provides a deeper understanding of how digital marketing strategies can be harmonized with Islamic ethical and economic principles. The findings are expected to offer valuable insights for MSME business managers, academics, and policymakers in leveraging social media marketing while adhering to Maqashid asy-sharia values. This research contributes to the discourse on digital marketing in the context of Islamic economic principles and serves as a foundation for future studies exploring ethical business practices in the digital era.